"واقع التمويل بالاعتماد الايجاري في الجزائر (دراسة حالة بنك البركة الوادي) " - دهانة بشير; وليد عريق; نسيم صالحي (جامعة الوادي University Of Eloued, 2024)
"تهدف هذه الدراسة إلى التعرف على تقنية الاعتماد الايجاري باعتبارها من الوسائل المعتمدة في تمويل المشاريع الاقتصادية، خصوصا ما تمنحه للمستأجرين من مزايا تتمثل بالأساس في التمويل الكلي دون الحاجة للتمويل الذاتي. ومن أجل ذلك اتبعنا أسلوب دراسة الحالة في الجانب التطبيقي عبر زيارة ميدانية على مستوى بنك البركة وكالة الوادي، باعتباره يعتمد على تقنية الاعتماد الايجاري في تمويل المشروعات، واعتمدنا في الدراسة التطبيقية على أداة المقابلة لجمع المعلومات اللازمة مع دراسة حالة تمويل بالاعتماد الايجاري لأصول منقولة لشركة ذات مسؤولية محدودة تمت على مستوى الولاية. وقد توصلت دراستنا هذه إلى أن الممارسة العملية لتقنية الاعتماد الايجاري في تمويل المشاريع الاقتصادية في الجزائر وبالتحديد في بنك البركة الجزائري لا تترك للعميل حرية التفاوض في شروط العقد، بل هي عبارة عن عقود نموذجية معدة مسبقا في شكل عقود اذعان حسب القانون، كما أن ارتفاع تكلفة عملية الاعتماد الايجاري مقارنة بالقروض الممنوحة من طرف البنك، اضافة لعدم قدرة المستأجر على فسخ العقد كون البنك يورد منقولات خصيصا للمستأجر ولا يمكن اعادة تأجيرها لمؤسسة أخرى. " "This study aims to identify the technique of leasing as one of the approved means of financing economic projects, especially the advantages it offers to lessees, which mainly include total financing without the need for self-financing. In order to achieve this, we followed a case study approach in the practical aspect through a field visit to Banque Al Baraka, EL-oued Agency, as it relies on the technique of leasing in project financing. In the empirical study, we relied on the interview tool to gather the necessary information, along with a case study of leasing financing for movable assets for a limited liability company at the state level. Our study has concluded that the practical application of leasing in financing economic projects in Algeria, specifically at Banque Al Baraka Algerian, does not leave the client the freedom to negotiate the contract terms, but rather involves pre-prepared standard contracts in the form of consent contracts according to the law. Additionally, the cost of the leasing process is higher compared to loans granted by the bank, and the lessee is unable to terminate the contract as the bank specifically provides the assets to the lessee and they cannot be re-leased to another institution. "
مذكرة ماستر
Keywords: اعتماد الايجاري; مؤجر; مستأجر; مورد; بنك البركة وكالة الوادي.; leasing; lessor; lessee; supplier; Al Baraka Bank Oued Agency.